Analisa Strategi Pemasaran Produk Layanan Emas Prespektif Syariah Marketing di Bank Syariah Indonesia Kantor Cabang Bandar Jaya - Siswoyo; M. Muslih; Annikmah Farida; Nur Alfi Khotamin; Rita Rahmawati; Eka Nurzannah; Uswatun Hasanah; Ika Trisnawati A; Ikhwanudin (Bulletin of Community Engagement, 2024)
Along with the development of sharia-based financial institutions, the products offered are also developing, where currently sharia banking not only offers savings and financing products but also offers many other products such as gold pawning and gold installments. The reason for conducting this research is because this gold service product is classified as a new product and customer interest in applying for this product increases every year. To research and process the data in this research, the researcher used a qualitative approach method with the type of research being descriptive. The subject collection technique uses a purposive method. Data analysis uses descriptive methods. Where the data collection technique uses observation, documentation and interview methods. The results of this research state that: Marketing strategy for gold service products at Bank Syariah Indonesia KC. Bandar Jaya carries out the process of dividing markets, determining targets and continuing with the promotion process by introducing products and prices and improving service quality by implementing sharia principles such as justice, trustworthiness and communicativeness. Marketing strategy for gold service products at Bank Syariah Indonesia KC. Bandar Jaya's sharia marketing perspective is in accordance with marketing sharia which consists of: View Market Universally (segmentation), Target customer's heart and soul (targeting), Build a belief system (positioning). As well as implementing sharia principles in the form of fairness, trust and communication.